1979
DOI: 10.1246/bcsj.52.2581
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Berberine by Ion-pair Extraction-Titration, with Tetrabromophenolphthalein Ethyl Ester as the Indicator

Abstract: A method has been developed for the determination of berberine as a quinolizinium medicine. The method is based on the solvent extraction-titration of an ion pair. Sodium tetraphenylborate is used as the titrant, with tetrabromophenolphthalein ethyl ester as the indicator in the presence of chloroform. In the two-phase titration, the proposed procedure gives sharp end points as the organic phase changes from blue to yellow. The aqueous phase is colorless throughout the titration. From a p(berberine)-pH diagram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In the literature, the berberine cation has been associated with various organic and inorganic anions, ,, and it has been observed that many of these water-soluble salts easily gave nice single crystals, the structure of which has been reported. In the present paper, our idea was to associate the berberine cation with a carboxylate anion provided with a long alkyl chain, specifically palmitate, in order to obtain a hydrophobic salt (Figure ) and with the hope that this salt would crystallize in water. The following work describes the preparation and characterization of berberine palmitate, as well as its spectroscopic behavior in solution and in the solid state.…”
Section: Introductionmentioning
confidence: 95%
“…In the literature, the berberine cation has been associated with various organic and inorganic anions, ,, and it has been observed that many of these water-soluble salts easily gave nice single crystals, the structure of which has been reported. In the present paper, our idea was to associate the berberine cation with a carboxylate anion provided with a long alkyl chain, specifically palmitate, in order to obtain a hydrophobic salt (Figure ) and with the hope that this salt would crystallize in water. The following work describes the preparation and characterization of berberine palmitate, as well as its spectroscopic behavior in solution and in the solid state.…”
Section: Introductionmentioning
confidence: 95%
“…The two-phase ion-association titration was applied to the determination of some basic pharmaceutical compounds using indicators for visible end-point detection. Earlier, the end-point detection in this type of titrations was based on the movement of the indicator from one phase to other and it was difficult to detect the end point because the color of the indicator in the aqueous phase or organic phase will be reflected in the other phase [39]. The use of hydrophobic indicator is an alternative approach, which remains in the organic phase throughout the titration and gives a very sharp color change [40].…”
Section: Resultsmentioning
confidence: 99%
“…The method provides a simple operation to quantitativly analyze berberine. This method, for example, has better sensitivity for berberine than the assay of berberine in bulk aqueous solution with optical fiber sensor [16,17,18], titrimetry [5,6], and spectorfluorimetric [13] methods. Although, spectrofluorometry [14,15] involving liquid-liquid extraction is sensitive, it requires large amounts of organic solvent.…”
Section: Discussionmentioning
confidence: 99%
“…There are many methods for its assay in plant extracts and in pharmaceutical preparations such as titrimetry [5,6], spectrophotometry [7,8,9,10], TLC [11] and HPLC [12]. These methods, however, have suffered from drawbacks such as being tedious, time-consuming and of low sensitivity.…”
Section: Introductionmentioning
confidence: 99%